FAMILY ACTIONS TO OVERCOME THE SIDE EFFECTS OF CHEMOTHERAPY IN PATIENTS AT HOME - Yuyun Bella Ria Br Batubara; Rani Lisa Indra; Lita Lita (Poltekkes Kemenkes Semarang, 2022)
To cancer patients, families are the first home care and support providers who help meet all their needs. This study aims to define their actions that help the patients deal with the side effects of chemotherapy at home. This is a descriptive quantitative research involving cancer outpatients who are taking chemotherapies in Arifin Achmad Hospital of Riau Province. A consecutive sampling technique obtained 134 families as samples, from which the data were collected using a questionnaire and analyzed univariately. The results showed several major actions in helping their members get through the side effects of chemotherapy, which include helping overcome nausea and vomiting by providing preferable food (in as many as 84 patients or 63%), helping overcome hair loss by keeping hair short and easy to manage (in as many as 54 patients or 40.5%), helping overcome fatigue by assisting to manage routines (in as many as 83 patients or 62.2%), helping battle appetite loss by preparing favorite foods on demand (in as many as 99 patients or 74.2%), and helping overcome diarrhea by giving 8-10 glasses of water per day (in as many as 91 patients or 68.2%). These actions have given proper results in helping the patients overcome chemotherapy side effects at home. Therefore, our study is expected to be a reference for other families whose members are dealing with similar conditions.